Baudrillard's Theory of Simulation and Death of Real in Buried Child by Sam Shepard (Zien Journal of Social Sciences and Humanities, 2022)
Analyzing literary works through philosophical theories has attracted a lot of attention. Postmodern plays are of excessive popularity in this regard. Sam Shepherd's Buried Child which was published in 1978 is regarded as one of the most imperative plays in which Shepherd has portrayed the disappointment and disillusionment of the American Dream as a metanarrative that has been shattered. This research intends to approach Buried Child through Baudrillard's theory of simulation and death of real in order to see how diverse characters are escaping the reality because of the cynicism caused by the concept of American Dream. This research is going to show the close association between Baudrillard's hypothetical attitudes towards the subject of simulations and capitalism in the post-war America. It can be concluded that as Baudrillard (1988) believed, "It is no longer a question of a false representation of reality (ideology), but of concealing that fact that the real is no longer real, and thus of the saving the reality principle" (p. 172). Thus, the whole story of the buried child signifies the reality attitude and simulacrum because Shepherd meant his audience to recognize the absence of reality.